Prevalence and factors associated with dental caries and to occlusopathies in children from 3 to 8 years old (Research, Society and Development, 2022)
Dental caries and malocclusions are the main to serious health problems, have multifactorial public health characteristics, as they are significant changes in quality of life. The objective of the research was to identify a prevalence of dental caries and malocclusion in children aged 3 to 8 years old in the Children's Clinic II discipline of the Clínica Escola do Curso de Odontologia, Universidade Federal de Campina Grande (UFCG), campus Patos, Paraíba (PB). This was a cross-sectional, observational study, with an inductive, descriptive method and a qualitative approach, adopting as a data collection strategy for documental analysis of medical records accesses encompassing the following axes: demographic variables (gender, age and school), to dental services, oral hygiene habits, deleterious habits, eating habits, dental caries index and occlusion examination. From the medical records, it was observed that an experience of dental caries was 72.9%, considered a high prevalence, with an ceo-d index of 5.16 and CPO-D of 3.78. Regarding malocclusions, a prevalence of prevalence was also found, as 60.2% of the children had an occurrence of occlusion, with a prevalence of 52.1% in the occluded dentition and 64.7% in the mixed dentition. Most well, it was observed that most children with defect had it during brushing and high consumption of sweets and industrialized foods was not performed. And most with those who had a short duration also of maternal age.